2008
DOI: 10.1111/j.1365-2214.2008.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Toilet training in Turkey: the factors that affect timing and duration in different sociocultural groups

Abstract: Toilet training shows differences among cultures. The age of initiation may be increased as the parents are educated better and a child-orientated approach becomes more popular than the parent-orientated approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 12 publications
(43 reference statements)
2
17
2
11
Order By: Relevance
“…8 In this study, mean initiation and completion ages were 22.1±6.7 vs 28.1± 8.4 months, respectively. Their study showed that earlier initiation and longer duration of TT were observed among families living in rural and semiurban settlements, mothers educated for less than 5 years, unemployed mothers, children living in houses with an outside toilet, families using washable diapers or squat toilet.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 In this study, mean initiation and completion ages were 22.1±6.7 vs 28.1± 8.4 months, respectively. Their study showed that earlier initiation and longer duration of TT were observed among families living in rural and semiurban settlements, mothers educated for less than 5 years, unemployed mothers, children living in houses with an outside toilet, families using washable diapers or squat toilet.…”
Section: Discussionmentioning
confidence: 99%
“…11 Most studies show that the initiation age of TT has changed in the majority of the population during the past 60 years and is later when compared to the past. [7][8][9][10] This situation may have arisen due to the introduction of disposable diapers and wider acceptance of child-orientated approach training techniques. On the other hand, there is some evidence to suggest that more disorders of elimination such as urge incontinence, daytime wetting, constipation, stool toileting refusal may develop in children who are trained later.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations